Role of fast-ion transport manipulating safety factor profile in KSTAR early diverting discharges. (13th October 2020) - Kang, J.; Rhee, T.; Kim, J.; Podestà, M.; Bardóczi, L.; Nazikian, R.; Cheng, C.Z.; Kramer, G.J.; Choi, M.J.; Hahn, S.H.; Han, H.; Woo, M.H.; et al.
Abstract: Magnetohydrodynamics (MHD) activity is analyzed for a particular KSTAR discharge category, the main features of which are a high- q m i n and a broad q profile. An interesting finding in this scenario is that a steady-state high- q m i n and broad q profile has been constructed even without a strong off-axis current drive scheme. Time traces of magnetics spectrograms and electron cyclotron emission imaging (ECEI) clearly show that Alfvénic type MHD activity appears as a high- q m i n and broad q profile is formed. Conversely, this activity disappears as the current profiles evolve toward a low- q m i n profile. In this study, the effect of MHD modes and accompanying fast-particle transport on the formation of various current profiles is explored. The frequency patterns of the magnetics spectrograms and ECEI coherence are compared using a NOVA analysis to determine which series of Alfvénic modes are active. Then, the kick-model is applied to potential modes, and used to estimate how much fast-ions are transported and beam driven current profiles are varied. By comparing the reconstructed total current profile from the kinetic EFIT with the beam-driven current profile estimated from the kick model, it is determined how energetic particle transport is responsible for maintaining the safety factor profile and which q profile can provide high β N operation.